Meningkatkan Kemandirian Anak Usia 3 – 4 Tahun Melalui Metode Pembiasaan - Rumbrawer, Naumi; Wijayaningsih, Lanny (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Abstrack This research aims to increase the independence of children aged 3–4 years at the Shabat Hodu Lah Yahweh Kopeng school, Semarang Regency. found several behaviors that are not in accordance with the child's independence, namely: a). The child is unable to take off his shoes and does not put them on the shoe rack, b). Disposing of trash in the wrong place. c). Children cannot clean up their own toys. d). Children still depend on their parents. f). The method used is class action research method (Classroom Action Research). The researcher used a qualitative description method, the results of cycles I to II, the researcher used data trigulation - data collected obtained from researchers and peer teachers. The conclusion based on the results of the recapitulation of aspects in the habituation method can be seen that the activity aspects are developing well, so that parents and teachers can work together in increasing children's independence. Keywords: Independence, Early Childhood, Habituation Method